The Relationship between an Accessory Maxillary Ostium and Variations in Structures Adjacent to the Maxillary Sinus without Polyps - Serindere, Gozde; Gunduz, Kaan; Avsever, Hakan (International Archives of Otorhinolaryngology, 2022)
Introduction The maxillary sinus and its variations are very important to dentistry and rhinology.Objective To investigate the effect of the accessory maxillary ostium (AMO) on the variations of adjacent structures of the maxillary sinus.Methods The computed tomography (CT) images of 400 patients were retrospectively evaluated. The prevalence of AMO was calculated. The relationship between morphological variations of adjacent structures of maxillary sinus such as agger nasi cell (ANC), Haller cell (HC), nasal septum deviation (NSD), hypertrophy of inferior concha (HIC), pneumatization of middle concha (PMC), mucus retention cyst (MRC), mucosal thickening (MT), and maxillary sinusitis (MS), as well as the presence of AMO, were investigated.Results Presence of AMO was diagnosed in 42 patients (10.5%), having been found in 4.5% of the patients only on the right side, in 1.25% of the patients only on the left side, and in 4.75% of the patients on both sides. There is an increasing incidence of ANC, HC, NSD, HIC, and PMC in the presence of AMO and MS. There is a decreasing incidence of MRC in the presence of AMO. Furthermore, AMO does not affect the incidence of MT.Conclusion This study showed that most parameters, except for MRC and MT, had increasing incidence in the presence of AMO. It is important for radiologists and rhinologists to have knowledge about the location of AMO and the presence of variations of MS adjacent structures to avoid surgical complications.
Keywords: computed tomography; paranasal sinuses; sinus anatomy; sinusitis